Inheritance of fecundity and fertility in silkworm, Bombyx mori L. from all possible crosses between a set of parental lines (University Journal of Zoology, Rajshahi University, 2007)
Key words: Bombyx mori; diallel cross; fecundity; fertility Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 69-72